Strengthening The Academic Atmosphere In Higher Health Education With Character And Social Responsibility - Aulia Hervy Anggraeni; Haura Karlina; Ratna Utami Wijayanti; Wahyu Wismanto Hadi (International Journal of Health and Pharmaceutical (IJHP), 2022)
Education is a systematic process to improve human dignity holistically, which allows the three most elementary dimensions of humanity above to develop optimally. Thus, education should be a strategic vehicle for efforts to develop all the potential of individuals, so that the ideals of building Indonesian people as a whole can be achieved. The development of national education in the future is based on the paradigm of building Indonesian people as a whole, which functions as subjects who have the capacity to actualize the potential and dimensions of humanity optimally.build the portion of curricular activities with extra-curricular activities in Campus that are getting closer to balance. The existence of student organizations in Campus will be able to involve students in the development and self-actualization, as well as improve student competitiveness. culture and empowerment of students that take place must be able to give an example, build willpower, and develop student creativity in the learning process, through developing a cultural scheme of reading, writing, and arithmetic for all citizens, as Community Empowerment. The problem of the nation's strength lies in the capacity and capability of the generation, the purpose of higher education related to character building is basically to encourage the birth of good people. Students who have a positive character will have an attractive personality, ethical, unpretentious, honest, intelligent, caring, and tough. The campus atmosphere will be able to grow and develop good character will encourage students to grow with the capacity and commitment to do the best things and do everything with purpose. Students with good character will do their best as an offering to God Almighty, by optimizing their potential and accompanied by full awareness.